The Relationship of Attitudes Toward Recreational Reading in English and Attitudes Toward Academic Reading in English with Reading Achievement of Grades 3 to 5 English as a Foreign Language Students at an International School in Bangkok, Thailand - Valenciano, Adelynne Tuliao; Lynch, Richard (Scholar: Human Sciences, 2021)
The purpose of this study was to determine the relationship among attitudes toward recreational reading in English and attitudes toward academic reading in English with reading achievement of Grades 3 to 5 English as a foreign language for students at an international school in Bangkok, Thailand. The Elementary Reading Attitude Survey (ERAS) was used to collect data from 24 Grade 3 students, 20 Grade 4 students, and 23 Grade 5 students during the first term of 2018-2019. Descriptive statistics such as means, standard deviations, and Pearson product-moment correlation coefficient were used to analyze the data. The findings showed that Grades 3 to 5 students at this school had a high level of attitudes toward both recreational reading in English and academic reading in English. Attitudes toward recreational reading in English were found to correlate significantly with attitudes toward academic reading in English, while reading achievement did not significantly correlate with students’ reading attitudes in English. Recommendations for practice and future research are provided.